Dampak Negatif Tekanan Belajar terhadap Perkembangan Anak Usia Dini di Raudatul Athfal Mawadah Warahmah Medan - Hani Almaida Yanni (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study aims to analyze the negative impact of learning pressure on early childhood development at Raudhatul Athfal (RA) Mawadah Warahmah Medan. The background of this research is based on the increasing academic demands on early childhood, particularly in reading, writing, and arithmetic skills, which are often inconsistent with their developmental stages. The research employed a qualitative method with data collection techniques including observation, interviews, and documentation. The results show that learning pressure negatively affects several aspects of child development, such as causing learning stress, reducing intrinsic motivation, limiting creativity, and hindering social- emotional growth. These findings emphasize that early childhood education should focus on play-based approaches, exploration, and holistic potential development rather than solely on academic achievement. The contribution of this research is expected to provide valuable insights for teachers, parents, and educational institutions regarding the importance of reducing academic pressure and implementing learning methods aligned with the principles of early childhood education.